Pubic Hair Grooming and Sexually Transmitted Infections: A Clinic-Based Cross-Sectional Survey - Gaither, Thomas W; Fergus, Kirkpatrick; Sutcliffe, Siobhan; Cedars, Benjamin; Enriquez, Anthony; Lee, Austin; Mmonu, Nnenaya; Cohen, Stephanie; Breyer, Benjamin (Sexually transmitted diseases, 2020)
Pubic hair grooming has been correlated with a self-reported history of sexually transmitted infections (STIs). We examined this relationship further in a cross-sectional survey of patients attending an urban STI clinic in San Francisco in 2018. Pubic hair grooming practices and detailed sexual histories were obtained. Sexually transmitted infections were confirmed via laboratory diagnosis or physical examination by a licensed provider. A total of 314 individuals completed the survey. The median age of participants was 31 years. In total, there were 247 (80%) men, 58 (19%) women, and 5 (2%) transgender participants. Of the 247 men, 177 (72%) identified as gay or bisexual. Twenty-five (82%) of 314 patients reported pubic hair grooming within the past 3 months. Seventy-eight (25%) patients were diagnosed with a new STI during their visit. There were no significant associations between reporting any anal or genital grooming and being diagnosed with an STI. However, anal groomers were 3 times as likely to be diagnosed with a rectal STI after adjustment (adjusted odds ratio, 3.0; 95% confidence interval, 1.2-7.5) compared with genital only groomers and nongroomers. Participants who report removing all of their pubic hair more than 6 times within the past year had higher prevalence of genital STIs (33.3%, 6-10 times; 28.6%, >10 times) compared with participants who never groom all of their pubic hair (15.3%, P = 0.01). We found no association between recent grooming and genital STIs. Anal grooming was associated with rectal STIs in gay and bisexual men.